Uremic Medium Disturbs the Hemostatic Balance of Cultured Human Endothelial Cells - Serradell, Mireia; Díaz-Ricart, Maribel; Cases, Aleix; Zurbano, María J.; Aznar-Salatti, José; López-Pedret, José; Ordinas, Antonio; Escolar, Ginés (Thrombosis and Haemostasis, 2001)
We have investigated the ability of serum from uremic patients to modify the thrombogenic properties of the endothelium. The effects of uremic medium on the morphology of endothelial cells (ECs), and their resistance to flow was analyzed. The influence of uremic media on the reactivity of the extracellular matrix (ECM) generated by ECs towards normal platelets was evaluated in a parallel-plate perfusion chamber. Exposure of ECs to uremic medium resulted in abnormal cell morphology and signs of an accelerated growth. Detachment of ECs exposed to circulating blood was increased when cells had been grown with media supplemented with uremic serum (21% vs. 14% non exposed). Platelet deposition was significantly elevated on ECMs generated in the presence of uremic media (uremicECMs) (p<0.01 vs. control studies). Effects of uremic serum were not observed at short incubation periods (5 h) but were evident after 24 or 72 h of incubation. Northern blot analysis revealed increased expression of tissue factor (TF) mRNA in ECs exposed to uremic conditions. Immunocytochemical methods detected an augmented expression of TF antigen on uremic ECMs. Incubation of ECMs with an antibody to human tissue factor prevented the increase in platelet deposition observed in uremic ECMs, suggesting that the presence of TF in ECM could be responsible for the enhanced platelet deposition. Results from our study indicate that uremic medium impairs the antithrombotic functions of cultured endothelial cells.
Keywords: Uremia; endothelial cells; tissue factor; hemostatic balance; atherothrombosis